Fecal calprotectin, lactoferrin and morbidity associated with immature digestive tract in preterm infants - D.S. Dobryk; D.O. Dobryanskyy (Group of Companies Med Expert, LLC, 2022)
Introduction. Excessive intestinal inflammation in preterm infants is one of the key factors in the development of necrotizing enterocolitis (NEC), early- (EOS) and late-onset neonatal sepsis (LOS). Purpose - to evaluate the connection between fecal calprotectin (FC), enteral use of lactoferrin (LF), and the occurrence of NEC, EOS, and LOS in preterm infants. Materials and methods. FC was measured in 26 newborns with gestational age (GA) ≤32 weeks and birth weight ≤1500 g. Feces were collected twice: in the first 7 days of life and at the postmenstrual age (PMA) of 36 weeks. The main group included 15 infants with either EOS, LOS or NEC. The remaining 11 infants formed the comparison group. Eleven infants received LF (4 in the main group and 7 in the comparison group), which was randomly administered in the first 3 days of life. Results. FC in the first 7 days of life was higher in the main group (р>0.05). At the PMA of 36 weeks, FC decreased in the main group and increased in the comparison group (p>0.05). FC in the first week of life was higher in infants with EOS compared to newborns without the diseases (p=0.03), followed by a decrease at the PMA of 36 weeks (p=0.04). There was no significant difference in FC levels depending on the development of LOS or NEC. FC levels increased in all infants who received LF and decreased in babies who did not receive LF (p>0.05). Conclusions. The occurrence of EOS is associated with a significant increase in FC which subsequently decrease by the PMA of 36 weeks. FC in the first week of life are not associated with the development of NEC or LOS. Enteral use of LF at a dose of 100 mg/day is associated with an increase in FC levels (p>0.05). The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.